Zionist Israel and the Question of Palestine : Jewish Statehood and the History of the Middle East Conflict - Amar-Dahl, Tamar (2017)
After half a century of occupation and tremendous costs of the conflict, Israel is still struggling with the idea of a Palestinian state in what is often perceived as the Biblical Eretz Israel. Mapping Zionism, enemy images, peace and war policies, as well as democracy within the Jewish State, the present study offers original insights into Israel’s role in this conflict. By analyzing Israeli history, politics and security-oriented political culture as it has been evolving from 1948 on, this book reveals the ideological and political structures of a Zionist-oriented state and society. In doing so, it uncovers the abyss between the Zionist vision of Eretz Israel on the one hand and the aspiration to achieve normalization, peace and security on the other. In view of this conflict-laden bi-national reality, the Palestinian question is identified as the Achilles‘ heel of Jewish statehood in the Land of Israel. Thus, Zionist Israel and the Question of Palestine provides a fresh, innovative, critical and yet accessible perspective on one of the most controversial issues in contemporary history